Modifiable risk factors related to burnout levels in the medical workplace in Taiwan: cross-sectional study - Yi-Sheng Liou; Yu-Li Lin; Cing-Hua Chen; Wei-Min Chu; Sung-Yuan Hu; Yi-Chien Yang; Yu-Tse Tsan (BMJ Open)
Objectives To detect the combined effects of lifestyle factors on work-related burnout (WB) and to analyse the impact of the number of weekend catch-up sleep hours on burnout risk in a medical workplace.Design Cross-sectional study.Setting Hospital-based survey in Taiwan.Participants In total, 2746 participants completed the hospital’s Overload Health Control System questionnaire for the period from the first day of January 2016 to the end of December 2016, with a response rate of 70.5%. The voluntary participants included 358 physicians, 1406 nurses, 367 medical technicians and 615 administrative staff.Primary and secondary outcome measures All factors that correlated significantly with WB were entered into a multinomial logistic regression after adjustment for other factors. The dose–response relationship of combined lifestyle factors and catch-up sleep hours associated with WB was explored by logistic regression.Results Abnormal meal time (adjusted OR 2.41, 95% CI 1.85 to 3.15), frequently eating out (adjusted OR 1.49, 95% CI 1.12 to 1.97), lack of sleep (adjusted OR 5.13, 95% CI 3.94 to 6.69), no exercise (adjusted OR 1.41, 95% CI 1.10 to 1.81) and >40 work hours (adjusted OR 2.72, 95% CI 2.08–3.57) were independently associated with WB (for high level compared with low level). As the number of risk factors increased (1–5), so did the proportion of high severity of WB (adjusted OR 1.39, 95% CI 0.45 to 4.27, to adjusted OR 32.98, 95% CI 10.78 to 100.87). For those with more than 7 hours’ sleep on workdays, weekend catch-up sleep (≤0/>0 and ≤2/>2 hours) was found to be related to an increase of burnout risk (adjusted OR 4.91, 95% CI 2.24 to 10.75/adjusted OR 4.94, 95% CI 2.54 to 9.63/adjusted OR 6.74, 95% CI 2.94 to 15.46).Conclusion WB in the medical workplace was affected by five unhealthy lifestyle factors, and combinations of these factors were associated with greater severity of WB. Weekend catch-up sleep was correlated with lower burnout risk in those with a short workday sleep duration (less than 7 hours). Clinicians should pay particular attention to medical staff with short sleep duration without weekend catch-up sleep.